PENGARUH INDIKATOR FINANSIAL, UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Nur Aprilita Fauziyah, 15.05.52.0336; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze the influence of financial indicators, company size, institutional ownership, and managerial ownership of financial distress on manufacturing companies listed on BEI period 2014-2017. The population in this study is all manufacturing companies registered in BEI period 2014-2017. The sample selection used a purposive sampling method and obtained a sample of 250 companies. The analytical tool used in this research is logistic regression analysis.The results of the research show that leverage influence has positive significant of financial distress. Profitability, operating capacity, and company size have a significant negative effect on financial distress. While liquidity, sales growth, institutional ownership, and managerial ownership do not have a effect on financial distress.